PENGARUH PROFITABILITAS, LEVERAGE DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Ibrahim, Marsina; Bulutoding, Lince; Fadhillatunisa, Della (ISAFIR: Islamic Accounting and Finance Review, 2024)
Abstract: This research aims to determine the effect of profitability, leverage and capital intensity on tax aggressiveness moderated by the audit committee. The population in this research is basic chemical industry companies in the chemical sub sector listed on the Indonesia Stock Exchange in 2018-2022 using a purposive sampling technique. The data used in this research is secondary data accessed via www.idx.co.id. The data obtained in the research was 40 from 8 companies that met the criteria. The results of the regression analysis show that profitability and capital intensity have a negative and significant effect on tax aggressiveness. Meanwhile, leverage has no effect on tax aggressiveness. The audit committee moderating variable is able to moderate the relationship between profitability and capital intensity on tax aggressiveness, but the audit committee moderating variable has not been able to moderate the relationship between leverage and tax aggressiveness.